38 A training program to build capacity for cervical cancer prevention in Mozambique. (13th November 2020) - Salcedo, M; Varon, M; Varon, M; Baker, E; Baker, E; Osman, N; David, E; Rangeiro, R; Changule, D; Andrade, V; Oliveira, CM; Neves, A; et al.
Abstract : Introduction: Cervical cancer is the primary cause of cancer among women in Mozambique. There is a shortage of providers trained to deliver cervical cancer screening and manage pre-invasive lesions. We describe a training program to build local capacity to deliver quality cervical cancer prevention services in Mozambique. Methods: The program includes training courses led by faculty from the United States (US) and Brazil, and consists of lectures followed by hands-on training stations to practice colposcopy, cervical biopsy, ablation and loop electrosurgical excision procedure (LEEP) using innovative training models. Participants then perform the procedures in clinic with supportive supervision from the international faculty. The courses are complemented by monthly videoconference telementoring sessions, held in Portuguese using the Project ECHO® (Extension for Community Healthcare Outcomes) model. Results: From 2016 to 2020, 10 courses were held in the cities of Maputo (n=8), Beira (n=1) and Nampula (n=1). There were 347 participants with an average of 34 participants per course. The courses have recently transitioned from only international faculty to include Mozambican gynecologists, including two fellows from the IGCS Global Curriculum program. A total of 15 ECHO sessions were held with ~25 participants/session, 30 patient cases discussed and 14 lectures delivered. Conclusion: This collaboration between Mozambique, Brazil and the US is building local capacity to prevent cervical cancer through training, mentoring and support of local providers. Due to the COVID-19 pandemic, the courses are being transitioned to a virtual format led by the Mozambican doctors with the international faculty joining remotely.